2006
DOI: 10.1080/01674820600869006
|View full text |Cite
|
Sign up to set email alerts
|

Girls experiencing sexual intercourse early: Could it play a part in reproductive health in middle adulthood?

Abstract: The aim of the present study is to examine the possible relationship between experiencing early intercourse and reproductive health characteristics in midlife for women. The participants belonged to the Swedish longitudinal research program Individual Development and Adaptation (IDA) project. By the age of 14, the cohort consisted of 590 girls, whereas 522 gave information about the timing of their first sexual intercourse experience. Approximately 29 years later, when the women were 43 years old, a sub-cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 32 publications
2
20
0
2
Order By: Relevance
“…In a large Norwegian study, maternal and paternal education as well as family income significantly predicted early sexual debut among 15- to 16-year old adolescent girls, such that girls with lower parental education were more likely to experience coital debut by age 15 or 16 as compared to girls with higher parental education (Valle, Røysamb, Sundby, & Klepp, 2009). This trend is consistent with other studies conducted in the United States (Longmore, Manning, Giordano, & Rudolph, 2004), Sweden (Magnusson & Trost, 2006), and New Zealand (Paul, Fitzjohn, Herbison, & Vickson, 2000). …”
Section: Predictors Of Early Coital Debutsupporting
confidence: 92%
See 2 more Smart Citations
“…In a large Norwegian study, maternal and paternal education as well as family income significantly predicted early sexual debut among 15- to 16-year old adolescent girls, such that girls with lower parental education were more likely to experience coital debut by age 15 or 16 as compared to girls with higher parental education (Valle, Røysamb, Sundby, & Klepp, 2009). This trend is consistent with other studies conducted in the United States (Longmore, Manning, Giordano, & Rudolph, 2004), Sweden (Magnusson & Trost, 2006), and New Zealand (Paul, Fitzjohn, Herbison, & Vickson, 2000). …”
Section: Predictors Of Early Coital Debutsupporting
confidence: 92%
“…Although early coital debut has been linked with having sex with multiple partners (World Health Organization, 2006) as well with other problematic sexual health outcomes in adulthood (Magnusson & Trost, 2006), not all sexual episodes among early adolescents are inherently risky. It is possible that the health of a girl’s first sexual experience may depend more heavily upon the quality of her relationship with her sexual partner than the timing of her first experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional research has documented associations between age at first sex and subsequent psychosocial adjustment, but without methodologically controlling for preexisting differences in functioning. For example, early age at first sex has been linked to earlier leaving of the parental home, lower educational attainment, experiencing a pregnancy termination (either via abortion or miscarriage), and receiving medical treatment to facilitate pregnancy (Magnusson and Trost 2006); greater psychological distress among college women (Leitenberg and Saltzmann 2003); and experimentation with cocaine (Kandel and Davies 1990) and other substances (Mott and Haurin 1988;Dorius et al 1991). Also, Cauffman and Steinberg (1996) found that physical involvement with a boyfriend among seventh-and eighth-grade girls predicted disordered eating.…”
Section: Discussionmentioning
confidence: 99%
“…The potential risks associated with sexual behaviour among 15 year olds are mainly linked to the emotional and behavioural characteristics of this developmental stage. It is known that early sex has implications for self-perceptions, social status and future health behaviour 5 . Unprotected and poorly protected intercourse brings the risk of unintended pregnancy with its myriad of possible outcomes for this age group, including abortion, early motherhood and adoption -each of which presents educational, economic, social and health challenges [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%